2022
DOI: 10.3390/ijerph19031129
|View full text |Cite
|
Sign up to set email alerts
|

Energy Imbalance Gap, Anthropometric Measures, Lifestyle, and Sociodemographic Correlates in Latin American Adults—Results from the ELANS Study

Abstract: Overweight and obesity are often explained by an imbalance between energy intake and expenditure. This, in addition to metabolic effects, makes it difficult to assess the real state of individual energy balance. This study aims to analyze the energy gaps between intake and expenditure in the adult population of Latin America, as well as its relationships with sociodemographic variables and nutrition status, to draw an epidemiological perspective based on the trends observed. The energy imbalance gap was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Thus, if a negative number is obtained, it is because the EE exceeds the EI, whereas if the EI is above the EE, a positive number is obtained ( 5 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, if a negative number is obtained, it is because the EE exceeds the EI, whereas if the EI is above the EE, a positive number is obtained ( 5 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they are longitudinal rather than cross-sectional studies, which limits their applicability for direct comparison of results. On the other hand, the authors’ previous experience with adults in LA ( 5 ), found that overall EIG was positive, meaning people consumed more energy than they were expended. This was more pronounced in men and people with higher socioeconomic status.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Few studies have investigated the acute effect of exercise on people with overweight/obesity, a group that includes the majority of the Colombian adult population, owing to their sedentary behavior and poor health and diet (Ferrari et al, 2022; García et al, 2022). The need for more specific recommendations for at‐risk individuals prompted the present randomized crossover trial, which aimed which.…”
Section: Introductionmentioning
confidence: 99%